2015
DOI: 10.1007/s10546-014-9996-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Spray-Mediated Enhanced Enthalpy and Reduced Drag Coefficients in the Modelling of Tropical Cyclones

Abstract: The impact of new parametrizations for drag and air-sea enthalpy exchange on modelling the intensity of tropical cyclones with a numerical weather prediction (NWP) model is examined. These parametrizations follow from a model for the marine atmospheric boundary layer for high wind-speed conditions in the presence of spray droplets that originate from breaking wave crests. This model accounts for the direct impact of these droplets on the air-sea momentum flux through action of a spray force, which originates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…Starting with the same temperature of the surface water, they may also lose sensible heat to the atmosphere. Previous numerical studies to investigate the effect of sea spray on tropical cyclones and extratropical storms intensity have been carried out by, among others, Andreas and Emanuel [2001] and Zweers et al [2015]. Recent observations have further confirmed that enthalpy fluxes at the high winds present in a typhoon are likely dominated by spray [Richter and Stern, 2014].…”
Section: Sea Spraymentioning
confidence: 92%
See 1 more Smart Citation
“…Starting with the same temperature of the surface water, they may also lose sensible heat to the atmosphere. Previous numerical studies to investigate the effect of sea spray on tropical cyclones and extratropical storms intensity have been carried out by, among others, Andreas and Emanuel [2001] and Zweers et al [2015]. Recent observations have further confirmed that enthalpy fluxes at the high winds present in a typhoon are likely dominated by spray [Richter and Stern, 2014].…”
Section: Sea Spraymentioning
confidence: 92%
“…[], and Zweers et al . []. Recent observations have further confirmed that enthalpy fluxes at the high winds present in a typhoon are likely dominated by spray [ Richter and Stern , ].…”
Section: The Physical Processes We Explorementioning
confidence: 99%
“…A decade later, this notion was confirmed experimentally by Powell et al (2003) for hurricane conditions, who even suggested that wind drag decreases for wind speeds exceeding 30 m/s. Parameterisations of this effect were proposed by Hwang (2011 and Zweers et al (2015). It is noted that no firm evidence exists about the behaviour of wind drag for wind speeds above 30 m/s (Stoffelen 2015, personal communication) and that a conservative approach is to cap the wind drag at its maximum value reached at a wind speed of about 30 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for the biases is that the resolution of the model is not high enough to capture the wind speed change in the simulations. When a decrease of drag coefficient and increase of heat transfer were implemented into the numerical simulation in the study of Zweers et al (2015), the intensity of the tropical cyclones was overestimated. Sensitivity experiments show that the changes of SST have a big impact on the intensity of tropical cyclones.…”
Section: Discussionmentioning
confidence: 99%